Refinement of the acute inhalation limit test for inert, nano-sized dusts by an in silico dosimetry-based evaluation: case study for the dissolution of a regulatory dilemma - Stratmann, Heidi; Ma-Hock, Lan; Tangermann, Simone; Corley, Richard A. (Frontiers in Toxicology, 2023)
This case study aims to describe the dilemma faced when exposing rats to very high concentrations of fine, pulverulent materials for acute inhalation studies and to address the regulatory question of whether the effects seen here are relevant to humans and the subject of classification according to the Globally Harmonized System of Classification and Labeling of Chemicals (GHS). Many powders match the definition of nanomaterials in the EU; therefore, information on acute inhalation testing of powders up to the GHS cutoff of 5 mg/L is required. However, testing rats at such a high aerosol concentration can cause physical obstruction of the airways and even mortality by suffocation. Therefore, to evaluate whether the physical effects on airway obstruction in rats exposed to 5 mg/L for 4 hours and alternative exposures to 1 and 2 mg/L are relevant for humans, an in silico evaluation of aerosol deposition was conducted using the multiple-path particle dosimetry (MPPD) model. For this evaluation, actual exposure conditions for an organic, nano-sized pigment which produced 100% lethality in rats at 5 mg/L, but not at 1 mg/L, were used to assess the potential for airway obstruction in rats and accordingly in humans. As an indicator of the potential for airway obstruction, the ratio of the diameter of the deposited, aggregated aerosol to airway diameter was calculated for each exposure condition. For rats exposed to 5 mg/L for 4 h, approximately 75% of tracheobronchial and 22% of pulmonary/alveolar airways were considered vulnerable to significant or complete obstruction (ratios >0.5). In humans, an equivalent exposure resulted in just over 96% of human tracheobronchial airways that received deposited mass to airway diameter ratios between 0.3 and 0.4 (nasal) or 0.4 and 0.5 (oral), with no airways with ratios >0.5. For the pulmonary/alveolar region, ∼88% of the airways following nasal or oral breathing were predicted to have deposited aerosol diameter to airway diameter ratios <0.1, with no airways with ratios >0.5. Thus, the in silico results obtained for rats are in line with the pathological findings of the animal test. The predicted results in humans, however, affirm the hypothesis of a rat-specific high dose effect which does not justify a classification according to GHS.